Pendampingan Pelayanan Akupresur Pada Bayi dan Anak Di Klinik Pratama Rawat Inap Aisyiyah Pandaan-Pasuruan-Jawa Timur - Hanum, Sri Mukhodim Faridah; Widowati, Hesty; Arti, Widi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
Complementary therapy is an option for Aisyiyah Pandaan Islamic Inpatient Clinic to be opened, but the limited facilities and human resources so that it cannot be realized, and the intense competition in the health services around the clinic becomes a threat to the clinic if the service remains as before. Based on data from patient visits to services Maternal and Child Health in the Islamic Pratama and Inpatient Clinic Aisyiyah Pandaan there was a 28% decrease in 2019 compared to 2018. Based on these problems, the solution provided was through the development of complementary therapy services, one of which was acupressure therapy for infants and children remember the clinic already serves pregnancy and childbirth checks. Implementation of activities begins with the improvement of human resources competencies through the acupressure training for infants and children, facilitation opens acupressure complementary therapy services for infants and children and helps create promotional media to the community. The results of this activities are increasing the understanding and skills of health workers and increasing the quantity and quality of services. The conclusion of this community service activity is to make a positive contribution to improving health services at the Aisyiyah Pandaan Inpatient Clinic which in turn can support increasing the number of infants and toddler visits.